Eco-friendly High-Strength Refractory Concrete Containing Calcium Alumina Cement by Reusing Granite Waste as Aggregate - Kourosh Shirani (SpringerOpen, 2021)
Abstract Besides preventing valuable natural resources from going to waste, using stone waste from stone processing plants in concrete helps reduce environmental pollution and, therefore, offers a convenient route to sustainable development. The present study aims to use granite waste (GW) in high-strength refractory concrete. Sixteen high-strength refractory concrete mixes, including two water-to-binder ratios (W/B = 0.17 and 0.2), two silica-fume-to-binder ratios (SF/B = 0.15 and 0.2), two binder contents (B = 1200 and 1400 kg/m3), and two replacement ratios of silica sand by granite waste (GW/Agg = 0 and 50%) were designed and prepared with high-alumina cement (HAC). The concrete specimens were exposed to 1200 °C. Compressive and flexural strength and scanning electron microscopy (SEM) tests were performed on specimens of concrete mixes before and after heating. It was found that in specimens with high binder content (1400 kg/m3), replacing 50% silica sand with GW (GW/Agg = 50%) in refractory concrete improves compressive and flexural strengths by 3–15 and 4–24% before heating, respectively. It was also shown that using GW to replace silica aggregates in concrete specimens with a 1200 kg/m3 binder content not only did not undermine, but also improved the compressive and flexural strengths of refractory concrete after heating by 20–78% and 15–60%, respectively, as a result of sintering. Meanwhile, in the case of the concrete with 1400 kg/m3 binder content, adding GW exacerbated its loss of compressive and flexural strengths after heating due to little or lack of sintering.